(untitled) (Texas Journal of Philology, Culture and History, 2026)
The expanding use of digital technologies in education has fundamentally transformed learning environments, opening up new opportunities for personalization and enhancing learning effectiveness, but simultaneously increasing psychological risks. This article examines the psychological foundations of digital well-being in an educational context through the lens of self-regulation and healthy lifestyle development. Digital well-being is defined as a subjective sense of control over the use of digital technologies, a balance of online and offline activity, and psychological resilience in the digital environment. A comprehensive psychological and pedagogical model of digital well-being is proposed, encompassing motivational, cognitive-reflective, emotional-regulatory, behavioral, and socioenvironmental components. The article substantiates the need to incorporate digital well-being principles into educational policy, curriculum design, and psychological support systems as a prerequisite for a sustainable and health-oriented digital transformation of education.